Redesign Taman Kota Kabupaten Bogor Dengan Pendekatan Urban Landscape Design - PERMANA, IRFAN ADI; FATIMAH, INDUNG SITTI (Jurnal Arsitektur Lansekap; Vol.3, No.1, April 2017, 2017)
ABSTRACT Redesign Bogor District City Park with Urban Landscape Design Approach Urban landscape design is an approach on designing a city which gives positive impact on its civilians by providing a habitable environment. Urban landscape comes in many form, one of them is city park. City park one of the facilitation provided by the city where people can do several activities inside. A city park also serve as a landmark of the city. Bogor district has several parks with recreational function but not many city parks available that serves as a public space. One of them are a park located near the central government of Bogor district. The purpose of this study was to redesign a functional, aesthetic city park that could also be a landmark on the district. This study use spatial and descriptive analysis method. Keywords: Bogor district, city park, urban landscape design